Augmented Reality-Assisted Lift-the-Flap Books in Improving Science Learning Outcomes for Third Grade Elementary School Students - Putu Cindy Marcella; I Gede Margunayasa; I Wayan Widiana (Universitas Pendidikan Ganesha, 2026)
The low learning outcomes of elementary school students in science are influenced by the dominance of conventional learning methods, limited attractive learning media, and minimal integration of technology in the learning process. These conditions result in low student engagement and less than optimal understanding of concepts, especially in abstract material. This study aims to determine the effectiveness of the lift the flap book media assisted by augmented reality in improving elementary school students' science learning outcomes. This study is a development research that adapts the ADDIE model by involving third-grade students as research subjects. Data were collected through questionnaires and learning outcome tests using instruments that have met the criteria for validity and reliability. Data analysis was carried out using quantitative descriptive approaches, qualitative descriptive approaches, and inferential statistics to test the effectiveness of the developed media. The results showed that the media had a very good level of feasibility based on expert assessments, received very positive responses from practitioners, and was considered practical in its use by students. The effectiveness test showed a significant increase in learning outcomes after using the media. Thus, the lift the flap book media assisted by augmented reality proved feasible, practical, and effective for use in science learning. The implications of this research indicate that the integration of technology-based interactive media can improve the quality of learning, strengthen student engagement, and support the development of deeper conceptual understanding in the context of basic education.